Infrared nanospectroscopy reveals the molecular interaction fingerprint of an aggregation inhibitor with single Aβ42 oligomers - Francesco Simone Ruggeri (Nature Portfolio, 2021)
Our understanding of the molecular mechanisms underlying pathological protein aggregation remains incomplete. Here, single molecule infrared nanospectroscopy (AFM-IR) offers insight into the structure of Aβ42 oligomeric and fibrillar species and their interaction with an aggregation inhibitor, paving the way for single molecule drug discovery studies.